2015
DOI: 10.1108/bfj-05-2014-0183
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric relationships in networked agricultural innovation processes

Abstract: Purpose - In innovation networks, asymmetric relationships are both considered as an opportunity and a threat for the enhancement of innovation. The purpose of this paper is to investigate how much asymmetry Flemish farmers perceive in their relationships for innovation with colleagues, suppliers and buyers. Design/methodology/approach - In total, 86 farmers active in four different agricultural subsectors in Flanders were consulted, of which 38 via in-depth interviews and 48 in seven focus groups. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
1
5
1
6
Order By: Relevance
“…Second, the finding that respondents from all stages mentioned "connectedness" as a critical issue suggests a stronger awareness of upstream and downstream stakeholders and that extending support to other members of the chain can improve the collective value chain. This finding is in direct contrast to many industries, where the value chain members are much less concerned about the chain as a whole, but rather their own improvement (Mentzer et al, 2001;Lambrecht et al, 2015).…”
contrasting
confidence: 65%
“…Second, the finding that respondents from all stages mentioned "connectedness" as a critical issue suggests a stronger awareness of upstream and downstream stakeholders and that extending support to other members of the chain can improve the collective value chain. This finding is in direct contrast to many industries, where the value chain members are much less concerned about the chain as a whole, but rather their own improvement (Mentzer et al, 2001;Lambrecht et al, 2015).…”
contrasting
confidence: 65%
“…Considering that market power can be concentrated in the retail link and that this affects producers, governance structures such as cooperatives arise as a way to increase the bargaining power of the producer link, in addition to promoting the exchange of knowledge between agents (Bijman, 2009;Corte et al, 2015;Lambrecht et al, 2015;Malorgio et al, 2012).…”
Section: Hybrid Forms -Cooperativesmentioning
confidence: 99%
“…Generated innovations can change the characteristics of transactions since they can design a product/service with greater added value which can lead to greater asset specificity and dimensions which can be difficult to be evaluated and measured. Therefore, governance structures need to foster innovations (Lambrecht et al, 2015;Nain et al, 2019;Nijhoff-Savakki et al, 2012) while adequately enabling agents to distribute the value generated (Buainain & Batalha, 2007;Malorgio et al, 2012;Mancini et al, 2019).…”
Section: Governance Structure and Innovation To Create And Remunerate...mentioning
confidence: 99%
“…While contractual arrangements are necessary for the remuneration of the created value, found that such arrangements, both horizontal and vertical, are sources of innovations. The promotion of innovation in horizontal arrangements occurs due to cooperation, the possibility of reducing opportunistic behavior, and the greater flow of knowledge among agents (Lambrecht et. al., 2015;Nijhoff-Savakki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%